“Fuck Your Breath”: Black Men and Youth, State Violence, and Human Rights in the 21st Century - Dr. Jeremy I Levitt (Washington University Journal of Law & Policy, 2015)
This essay uses personal anecdotes to confront police brutality against Black people living in the United States, assesses both human rights implications and global response mechanisms to anti-Black violence, and proposes solutions to address this pervasive problem. Dr. Levitt calls upon Black people to become stakeholders in the fight for freedom by reconstructing a number of unfortunate dualities in the United States system that put the rights of whites above those of others. In conclusion, Levitt calls for change and a halt to “systematic maltreatment of African-Americans by police agencies.”
Keywords: racism; police brutality; human rights; Ferguson